2013
DOI: 10.1002/mnfr.201200617
|View full text |Cite
|
Sign up to set email alerts
|

The influence of folate supplementation on global gene expression in normal colonic mucosa of subjects with colorectal adenoma

Abstract: These results indicate that while folic acid can modify gene expression, it is difficult to separate its effects from the natural variability in gene expression in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Folic acid supplementation decreased methylation in c-myc and c-jun , thereby promoting the malignant phenotype of placental trophoblasts. Folic acid was observed to induce gene-specific positive and negative changes in promoter methylation and mRNA expression in our study, this is consistent with the earlier studies showing the dual effect of folic acid supplementation on the global gene expression in certain cancers ( 11 , 12 , 14 ). Additionally, folic acid dysregulation may affect gene expression also by inducing base substitution, DNA breaks, gene deletions, and gene amplification ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Folic acid supplementation decreased methylation in c-myc and c-jun , thereby promoting the malignant phenotype of placental trophoblasts. Folic acid was observed to induce gene-specific positive and negative changes in promoter methylation and mRNA expression in our study, this is consistent with the earlier studies showing the dual effect of folic acid supplementation on the global gene expression in certain cancers ( 11 , 12 , 14 ). Additionally, folic acid dysregulation may affect gene expression also by inducing base substitution, DNA breaks, gene deletions, and gene amplification ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…Further, folic acid supplementation is known to affect the transcription of various genes, with both enhancing and down regulating gene expression ( 11 , 12 ). is an association with its promoting or repressing effects on DNA and histone methylation ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 The epigenetic effects of folate supplementation in the presence of colorectal adenomas have been hypothesized. [17][18][19] In individuals with colorectal adenomas and normal folate levels at baseline, changes in tissue biomarkers associated with colon cancer in patients supplemented with folate have been assessed. P53 and DNA strand breaks in exons 5-8 demonstrated accelerated improvement over the first 6 months when compared with placebo, but this difference was not sustained on assessment at 1 year.…”
Section: B Vitaminsmentioning
confidence: 99%
“…Notably, there was no increase in adverse events in the supplemented group. 17 After considering the role of B vitamin supplementation in these scenarios, the route of administration may also be important. Specific to vitamin B 12 supplementation, there has been study of the efficacy of enteral vs intramuscular supplementation in patients following gastrectomy for gastric cancer.…”
Section: B Vitaminsmentioning
confidence: 99%
“…In fact, the altered DNA and RNA methylation, and the disruption of DNA integrity and repair, lead to DNA aberrations with a higher risk of developing cancers and in particularly the colorectal one [93]. Furthermore, the results of a randomized trial conducted on fourteen subjects with adenoma receiving 400 mcg/day or placebo for 10 weeks, indicated that folic acid can modify gene expression [94]. …”
Section: Folic Acidmentioning
confidence: 99%